El Concepto De Política En Alain Badiou ¨el siglo como crisis de sentido¨ (2010)
The following monographic work intends to call the attention on what is called the current political reason through the philosophical reflections of the French author Alain Badiou. The method to be used within this writing is basically interpretive/exegetic since Badiou‟s texts are approached without prior work in this academic context and its statements are subjected to corroboration and, at the same time, a deductive method is used since it begins from a general theme such as the general panorama of the contemporary French philosophy and the place of Badiou‟s thought within this philosophy up to learning how the current political reason configures itself, that is to say, what does Badiou‟s philosophy say about the state of the current politics and the answer to the question What politic is?